Purinergic Signaling to Terminate TLR Responses in Macrophages - Hamidzadeh, Kajal; Mosser, David M. (Frontiers in Immunology, 2016)
Macrophages undergo profound physiological alterations when they encounter pathogen associated molecular patterns (PAMPs). These alterations can result in the elaboration of cytokines and mediators that promote immune responses and contribute to the clearance of pathogens. These innate immune responses by myeloid cells are transient. The termination of these secretory responses is not due to the dilution of stimuli, but rather to the active down-regulation of innate responses induced by the very PAMPs that initiated them. Here we describe a purinergic autoregulatory program whereby TLR-stimulated macrophages control their activation state. In this program, TLR stimulated macrophages undergo metabolic alterations that result in the production of ATP and its release through membrane pannexin channels. This purine nucleotide is rapidly hydrolyzed to adenosine by ectoenzymes on the macrophage surface, CD39 and CD73. Adenosine then signals through the P1 class of seven transmembrane receptors to induce a regulatory state that is characterized by the down-regulation of inflammatory cytokines and the production of anti-inflammatory cytokines and growth factors. This purinergic autoregulatory system mitigates the collateral damage that would be caused by the prolonged activation of macrophages, and rather allows the macrophage to maintain homeostasis. The transient activation of macrophages can be prolonged by treating macrophages with IFN-γ. IFN-γ treated macrophages become less sensitive to the regulatory effects of adenosine, allowing them to sustain macrophage activation for the duration of an adaptive immune response.